Modern sociocultural space and regional journalism - Krasouskaya, Alena V. (Journal of the Belarusian State University. Journalism, 2019)
The article is devoted to the problem of forming modern socio-cultural space. The idea that the mass media actively participate in this process is substantiated. A special role is played by regional newspapers, which is confirmed by their high rating. Regional print media detail coverage of the state policy, which in the past 10 years is aimed at the introduction of innovations in all spheres of public life. The results of contentanalysis demonstrated the impact of regional newspaper on social life, which is expressed in spreading the idea of the value of innovations for Belarusian society. The article concludes that regional journalism reflects the changes that take place in the life of Belarusian society, forming a modern socio-cultural space, permeated with the idea of innovation.